Aplicación de un procedimiento para el control de gestión de la industria Genética Nacional S. A. - Alcívar Bermeo, Andrea Alexandra (2020)
The main objective of the research was to apply a procedure for management control in the National Genetic S.A. industry, as a contribution to decision-making. Outlining, a bibliographic review was applied in reliable sources and articles that allowed to base this research. With the applied methodology, the collection tools allowed an interview with the manager in order to characterize the company, learn about the organizational situation and determine the operation. The survey was then used to obtain qualitative data regarding management control; whose instrument contained 20 items, 5 questions corresponding to the perspectives of the balanced scorecard. Then, the information obtained was processed to know the current situation of the industry with respect to the four perspectives evaluated, and the multiple deficiencies found in the organization were also detailed using an Ishikawa diagram, achieving a broader visualization of the problems that prevent an efficient control management and convenient decision making. Concluding with the respective application of techniques and tools, relevant information corresponding to the current situation of the organization under study was obtained, the methodology of the balanced scorecard for management control was implemented, and finally it was evaluated by means of the traffic light or dashboard indicators for each perspective to measure the achievement of strategic objectives. Finally, an action plan was proposed, this tool being essential for meeting the organization's objectives and goals.